The Transportation Performance Analysis of Logistics for Perishable Foods in Greater Bandung - Hasriwan Putra; Herma Juniati; Sukma Rahadian (Institut Teknologi Sepuluh Nopember, 2020)
This article aims to analyze the transportation performance in logistics of perishable foods in Greater Bandung and to identify the product loss of mushrooms and cabbages. It can be concluded that the main factors influencing the performance of transportation for perishable foods are: (1) Transportation operating hours adjusted to harvest time and market opening time, (2) Trip routes divided by 2 are using the shortest/ closest route and using a toll road, (3) Type of vehicle depend on the scale of production, the scale of the order and the distance of the trip, (4) the sale of products from farmers according to the nearest market location. Transportation cost contributes about 2-5% of product price. And, main factor of transportation cost is load factor. For cabbage, there is a 20% product loss from farmers to traders in central/ traditional markets.